2020
DOI: 10.1002/eji.202048566
|View full text |Cite
|
Sign up to set email alerts
|

NCoR1 fine‐tunes type‐I IFN response in cDC1 dendritic cells by directly regulating Myd88‐IRF7 axis under TLR9

Abstract: Plasmacytoid dendritic cells (DCs) are reported to induce robust type-I interferon (IFN) response, whereas cDC1 DCs develop moderate type-I IFN response upon TLR9 stimulation. It is very interesting to understand how this signaling under TLR9 is tightly regulated for the induction of type-I IFNs. Here, we report co-repressor protein NCoR1 as the major factor fine-tuning the signaling pathways regulating IFN-β expression under TLR9 in cDC1 DCs. We found that NCoR1 knockdown induced a robust IFN-β-mediated antiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…However, further studies are needed to clearly identify these functions. [1351,1399,1429,1430]. While all cDCs express high levels of CD11c and MHCII across tissues, pDCs are rather CD11c int cells that are characterized by the expression of markers such as SiglecH, B220 and mPDCA-1, while lacking expression of CD11b.…”
Section: Key Information Human Vs Murine This Is Detailed Inmentioning
confidence: 99%
“…However, further studies are needed to clearly identify these functions. [1351,1399,1429,1430]. While all cDCs express high levels of CD11c and MHCII across tissues, pDCs are rather CD11c int cells that are characterized by the expression of markers such as SiglecH, B220 and mPDCA-1, while lacking expression of CD11b.…”
Section: Key Information Human Vs Murine This Is Detailed Inmentioning
confidence: 99%
“…We recently reported that NCoR1 acts as a direct repressor of tolerogenic and antiviral immune response genes upon TLR9 ligation in cDC1 [ 33 , 34 ]. TLR9 activated NCoR1 depleted cDC1 showed increased Il10 and Ifnb1 gene expression.…”
Section: Resultsmentioning
confidence: 99%
“…NCoR1/SMRT were originally identified in complex of unliganded thyroid receptor and retinoic acid receptor and were thought to mediate their repression activity with only nuclear receptors but later several studies have shown the repression through other transcription factors such as BCL6, Kaiso, FOXP1 [ 29 32 ]. We have reported in our previous studies that perturbation of NCoR1 in cDC1s leads to derepression exemplified by increase in expression of proinflammatory cytokines, anti-inflammatory cytokines as well as antiviral response genes upon TLR9 activation [ 33 , 34 ]. This suggests that NCoR1 mediated strong repression of genes under TLR activation is required to mount signal specific immune response.…”
Section: Introductionmentioning
confidence: 99%
“…Stable KD of Zbtb10 in cDC1 Mutu-DC line was generated using a lentivirus-mediated approach [45]. In brief, Lentiviral particle expressing shRNA transfer plasmid specific for Zbtb10 and empty vector (control shRNA) along with packaging plasmids (pCMVR8.74 and pMD2G) were produced in human embryonic kidney (HEK)-293 cells using Calphos kit (Clone tech).…”
Section: Development Of Stable Kd Of Zbtb10 In Cdc1 Mutu-dc Linementioning
confidence: 99%